2013
DOI: 10.1016/s1734-1140(13)71517-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress markers in affective disorders

Abstract: Affective disorders are a medical condition with a complex biological pattern of etiology, involving genetic and epigenetic factors, along with different environmental stressors. Increasing numbers of studies indicate that induction of oxidative and nitrosative stress (O&NS) pathways, which is accompanied by immune-inflammatory response, might play an important role in the pathogenic mechanisms underlying many major psychiatric disorders, including depression and bipolar disorder. Reactive oxygen and nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
77
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 94 publications
3
77
0
2
Order By: Relevance
“…This results in the production of free radicals, a high content of lipids (including unsaturated fatty acids) as a substrate for oxidation, an altered redox potential of a number of neurotransmitters, inefficient defense mechanisms against free radicals as well as a high concentration of metal ions (e.g. iron and copper) involved in redox reactions [1,2,4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in the production of free radicals, a high content of lipids (including unsaturated fatty acids) as a substrate for oxidation, an altered redox potential of a number of neurotransmitters, inefficient defense mechanisms against free radicals as well as a high concentration of metal ions (e.g. iron and copper) involved in redox reactions [1,2,4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…They have also shown changes in the activity of enzymes involved in the processes of free radical scavenging [6]. According to a meta-analysis, the most frequently observed and most intensified phenomenon which reflects oxidative stress in BD is an increase in thiobarbituric acid-reactive substances (TBARS), which are markers of lipid damage and peroxidation [21].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that oxidative and nitrosative stress pathways, along with immune-inflammatory response, might play an important role in the pathogenic mechanisms underlying major depression and bipolar disorder 1 . Reactive oxygen species affect both the immune-inflammatory pathways and the expression of key neurotransmitters which are involved in the pathophysiology of depression 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The ROS can damage DNA, proteins, and lipids, and change a cell's metabolism, and affect gene expression and post-translational modifications of proteins, which accelerates ageing, neurodegeneration, and development of atherosclerosis, hypertension, type II diabetes, and cancer [26,27]. Superoxide dismuthase (SOD) and glutathione peroxidase (GPx) are antioxidant enzymes ubiquitous in living organisms acting as an endogenous defense against ROS [28,29].…”
mentioning
confidence: 99%